Evaluasi Tingkat Risiko Kesehatan Dalam Metode Pengujian Emas Pada Laboratorium Mineral Xyz - Andra, Yoli; Modjo , Robiana (Syntax Corporation, 2025)
Gold testing at the XYZ Mineral Laboratory is a routine activity that uses chemicals that are hazardous to workers' health, including the fire assay method, aqua regia method, and cyanide leaching method. However, the hazard rating, risk rating, adequacy of controls, and comprehensive health risk assessment are currently unknown. By understanding these factors, laboratory management can establish preventive measures to avoid exposure to hazardous chemicals, prevent work-related illnesses, and determine gold testing methods with lower health hazard levels. The CHRA DOSH Malaysia (2018) method can be used to qualitatively assess inhalation, dermal, and ingestion exposure. The health risk comparison of gold testing using the aqua regia method has a lower risk rating with a value of 9 (Moderate Risk), compared to the fire assay method with a value of 25 (High Risk) and cyanide leaching with a value of 15 (High Risk). The dermal exposure risk rating for all three methods is H2 (High). This aligns with the highest hazard rating value for gold testing using the cyanide leaching method, with a value of 5. Health risk control for gold testing at the Mineral XYZ laboratory is currently adequate; however, gold testing using the aqua regia method and cyanide leaching method should be prioritized for further control measures.